Effectiveness of craniosacral therapy in musculoskeletal pain disorders - Kacper Pajor; Justyna Szpyt; Agnieszka Turoń-Skrzypińska; Iwona Rotter (Kazimierz Wielki University, 2020)
Introduction Craniosacral therapy is becoming more and more popular among therapists around the world. Its activity is based on primary respiratory mechanism (PSM), a natural craniosacral rhythm consisting of two phases: flexion and extension. During therapy, the therapist, using appropriate manual techniques performed with minimal force, restores the physiological craniosacral rhythm, restores the mobility of the cranial sutures and affects the mobility of the central nervous system. Due to not fully understood mechanisms of action and controversial foundations, the effectiveness of craniosacral therapy is often questioned. Purpose The purpose of this research review is to determine the effectiveness of craniosacral therapy on musculoskeletal pain disorders. Material and methods The PubMed database was searched using "Craniosacral therapy" for clinical trials and randomized clinical trials. Studies with other forms of therapy or placebo, conducted on newborns and older than 15 years and were excluded. These exclusions narrowed the search results to 5 works. Results Each study reported statistically significant improvement in at least one type of perceived pain in intervention group. In all studies, in at least two of the assessed tests (assessing pain and functionality), the difference between the result before the therapy and the result achieved after the therapy improved more for the group undergoing craniosacral therapy. Moreover, a review of studies showed insufficient level of research explaining the physiological foundations of craniosacral therapy. Conclusions 1. Craniosacral therapy can effectively reduce pain of musculoskeletal origin and increase the functionality of patients. 2. The mechanisms responsible for the effectiveness of craniosacral therapy and its theoretical foundations require further research.